PENGARUH SAHAM DAN REKSADANA SYARIAH TERHADAP PERKEMBANGAN EKONOMI INDONESIA SERTA INFLASI SEBAGAI VARIABEL INTERVENING - SAPIAH, SRI KASNELLY (Lembaga Penelitian dan Pengabdian Masyarakat IAI An-Nadwah Kuala Tungkal, 2021)
This research aims to determine whether or not there is an influence betweensharia shares and sharia mutual funds on economic development in Indonesia andthe inflation rate as an intervening variable. The method used in this research isquantitative with statistical path analysis. While data collection, using secondarydata sourced from the official website of the Financial Services Authority (OJK),Bank Indonesia (BI) and the Central Statistics Agency (BPS) in the form of annualdata, as well as from journals and e-books, then the data is processed using SPSSsoftware. version 26. It can be concluded that the influence between sharia sharesand sharia mutual funds on economic development and the inflation rate as anintervening variable partially has an effect, while simultaneously it has nosignificant effect, and that the magnitude of the influence of sharia shares andsharia mutual funds on economic development and the inflation rate is 41.7% andthe remaining 58.3% are thought to be found in variables other than those in thisstudy